Identification of Misconceptions and Causes of Misconceptions in Stoichiometry Material Using Four Tier Multiple Choice (4TMC) - Rahmawan, Setia; Ashfarini, Dyah (Orbital: Jurnal Pendidikan Kimia, 2024)
Stoichiometry is one of the materials in chemistry subjects in high school that contains basic concepts to understand other chemical concepts. At the same time, a few class X students need help understanding and even experience misconceptions. This study aims to identify subconcepts that experience misconceptions, the percentage of students who experience misconceptions, and the causes of misconceptions that occur in students. The research method used is the quantitative descriptive method. The sample of this study was students of grade X MIPA at SMA N 1 Jetis, which was taken based on purposive sampling techniques. The research instrument used was the Four Tier Multiple Choice (4TMC) diagnostic test instrument. The pattern of answers, reasons, and confidence rating from the Four Tier Multiple Choice (4TMC) test results are then processed and analyzed to obtain significant misconception data from students. The results of the research obtained, namely, there were misconceptions in stoichiometric material, especially in the subconcepts of Avogadro's Hypothesis, Proust's Law (Law of Fixed Comparison), Dalton's Law (Law of Multiple Comparison), Ar and Mr, the percentage of grade X students at SMA Negeri 1 Jetis on stoichiometric material who experienced misconceptions of 25.35% which was classified as a low category, as well as the causes of misconceptions experienced by grade X students at SMA Negeri 1 Jetis on the material This stoichiometry comes from teachers, learners, and books. Misconceptions originating from teachers are related to learning methods, techniques, and delivery. Misconceptions originating from students are caused by wrong conceptions of learners, dependent algorithmic phenomena, learners' abilities, and students' interests, which need to be improved. At the same time, the misconception from the book is the existence of inappropriate concepts in the student's notebook. Identifying these misconceptions is expected to be the first step to remediate student misconceptions on stoichiometric material and prevent prolonged misconceptions.